The Role of Green Infrastructure in Providing Urban Ecosystem Services: Insights from a Bibliometric Perspective - Milena V. Sokolova; Brian D. Fath; Umberto Grande; Elvira Buonocore; Pier Paolo Franzese (Land, 2024)
Urban ecosystems, and the services they provide, are a key focus of the United Nations 2030 Agenda for Sustainable Development, specifically SDG 11, which emphasizes making cities inclusive, safe, resilient, and sustainable. Green infrastructure (GI) is crucial in enhancing citizens’ quality of life and achieving this goal and it can be defined as a strategically planned network of natural and semi-natural areas designed to deliver a range of ecosystem services (ESs). These infrastructures improve ecosystem functioning, protect biodiversity, promote health, support sustainable land and water management, and boost the local green economy. This paper explores the scientific literature on GI and their ESs in cities using bibliometric science. By combining the keywords “Green Infrastructures”, “Ecosystem Services”, and “Cities” with VOSviewer software (1.6.20 version), we analyzed trends over time. Results show growing attention to these topics, emphasizing human well-being, urban resilience, and sustainability. The study also highlights that focusing exclusively on either “Green Infrastructure in Cities” or “Ecosystem Services in Cities” leads to fragmented insights. A more integrated examination of these three domains offers a holistic view and underscores the importance of considering ecosystem disservices. The study further identifies key research directions, including the need for a comprehensive evaluation of diverse GI types, especially those that are under-researched, such as green roofs, sports areas, and wetlands, and the underexplored role of cultural ecosystem services. Additionally, future research should consider both the benefits and disservices of GI to support better urban planning decisions. Finally, integrating biophysical, social, and economic values of ESs is critical for providing more holistic insights and enhancing sustainable urban development. The novelty of this paper lies in its integrated, holistic approach to examining GI and ESs in urban areas, with a focus on ecosystem disservices, insufficient attention to specific GI types, and the role of cultural ecosystem services—each contributing to the creation of more resilient and sustainable cities.